Effect of Low-Level Laser Therapy and Sinensetin (Combination therapy) on Tumor Cells (Hela) and Normal Cells (CHO): Combination Therapy on Tumor and Normal Cells - Javaheri, Behnam; Esmaeeli Djavid, Gholamreza; Parivar, Kazem; Hekmat, Azadeh (Journal of Lasers in Medical Sciences, 2021)
Introduction: Cervical and ovarian cancers are well-known causes of death among women in developing countries. There are various technologies to treat cancer cells, but the polyphenolic compound is a natural one and has an anti-cancer effect. In this study, we investigated combination therapy using sinensetin and low-level laser therapy (LLLT) to enhance treatment. Methods: The cancer cells purchased from Pasteur Institute, Iran, were cultured. The cells were treated with various concentrations of sinensetin, wavelengths of laser therapy (660 nm), and power density (3 J/cm2) for different times separately. Furthermore, the sensitivity of cells to sinensetin, LLLT, and combined therapy was determined by clonogenic assays. To measure DNA damage and repair at individual cell level used comet assay. To examine the intracellular generation of reactive oxygen species used 2′,7′-dichlorodihydrofluorescein (DCFH) as an intracellular probe. To analyze data we used SPSS software and comparison between groups was used (ANOVA) and t-test statistical analyses were performed using SPSS 17 software. The level of statistical significance was set at a two-tailed P value of 0.05. Results: Our results demonstrated that the doubling time for CHO is more than Hella cells, with 20.7 and 27.7 h for each cell respectively. The pretreatments can decrease the viability of both cell lines more than the first treatment. In the clonogenic assay, the pretreatment of cells with LLLT and Sinensetin significantly reduced the surviving fraction of both cell lines. MTT results showed that pretreatment with LLLT and Sinensetin can increase cell death compared to Sinensetin and LLLT alone. Conclusion: Our result indicated that combined therapy with LLLT and Sinensetin can treat CHO and Hela cells better than the other groups. Combination treatment with sinensetin-LLLT and the other treatment means, sinensetin and LLLT alone, did not change the cell viability significantly. DOI: 10.34172/jlms.2021.85.